Biblical principles towards a pastoral strategy for poverty alleviation amongst the youth in Uganda - Wilson, Asea (HTS teologiese studies, 2014)
Over centuries, many churches in Uganda have failed to do justice to the gospel to the materially and socially robbed. Their preoccupation has been with the gospel to the sinners. But the salvation of sinners and the care for the materially and socially deprived are part of one and the same gospel. In other words, these churches could not handle the two gospels that are found in the Bible: the salvation of the sinners and care for the physical needs of the poor. It has a gospel for the ‘sinning’, but no gospel for the ‘sinned against’. The church in Uganda must now become involved in the process of mutual commitment to freedom, justice and care for the disadvantaged. It must develop a complete theology of the divine grace for sinners as well as the gospel for the materially and socially disadvantaged. Moreover, however, eradicating material poverty is not simply a matter of making more and better provisions available, but of expanding actual participation so that young people might fulfil their own roles in the whole society to which they belong. An attempt was made to define poverty and to discuss the characteristics of poverty through the exposition of the weak points of both the church and the government that were constructed by means of a literature study as well as qualitative interviews in contrast to the biblical strength that was determined through an exegetical study of texts that specifically dealt with issues of poverty. The views of churches with regard to poverty were taken into consideration. Last but not least, a possible means was developed that could be utilised to break down the persistent poverty amongst the youth in Uganda.